Growth, Phenolic, and Flavonoid Production of Adenostemma platyphyllum at Different Dosages of Cow Manure - Ridwan, Taopik; Ananda, Fira; Maulana, Faizal; Takemori, Hiroshi; Azis, Sandra; Batubara, Irmanida (Jurnal Jamu Indonesia, 2024)
Adenostemma platyphyllum is a weed plant containing various secondary metabolites, such as phenolics and flavonoids, making it essential to cultivate properly. This study aims to determine the optimal cow manure dosage for plant growth, focusing on phenolic and flavonoid production in the cultivation of A. platyphyllum. The experiment employed a randomized complete block design (RCBD) with a single factor: cow manure doses of 0.5, 5, 10, 15, and 20 ton/Ha. Phenolic content was measured using the Folin Ciocalteu reagent, while flavonoid content was assessed using the AlCl₃ reagent. Results indicate that the highest phenolic and flavonoid production occurred in plants treated with 20 ton/Ha manure. This dosage also resulted in the best plant growth, yielding the highest crop, number of leaves, and branches compared to other treatments.